Caregiving activities causing occupational low back pain in Japanese social welfare facilities and hospitals - Kazuyuki Iwakiri; Keiichi Miki; Takeshi Sasaki (PLoS ONE, 2026)
Background Occupational low back pain (LBP) has increased in Japanese social welfare facilities and hospitals. Understanding its occurrence is the first step in addressing this issue. Aim This study investigated the caregiving activities that cause occupational LBP incidents in these contexts. Methods The study analyzed 2,722 incidents of occupational LBP among staff in social welfare facilities and hospitals resulting in four or more days absent from work. Data were extracted from accident occurrences and causes in the 2018–2019 Reports of Worker Casualties . The caregiving situations related to the occupational LBP incidents at each facility were then analyzed. Results Approximately half of the occupational LBP incidents surveyed occurred during transfer assistance. This assistance was mainly associated with eating, bathing, and toileting in both facilities and frequently occurred during patient transfers between a bed and a wheelchair. In social welfare facilities, nontransfer assistance also contributed significantly, which included bathing, toileting, childcare, diaper changing, lying, standing, sitting, walking, and car transportation. In hospitals, nontransfer assistance such as providing support for lying, diaper changing, medical care, and sitting were occupational LBP risk factors. Furthermore, most incidents of occupational LBP occurred among staff who worked alone during day shifts. Conclusion Caregiving activities involving transfer assistance, such as bathing, toileting, and eating, were common risk factors in social welfare facilities and hospitals. However, the specific nontransfer assistance activities contributing to occupational LBP varied by facility. To effectively reduce the incidence of occupational LBP, prevention strategies should focus on these high-risk activities according to facility type and the types of caregiving required.